Genetic Analysis and Species Specific Amplification of the Artemisinin Resistance-Associated Kelch Propeller Domain in P. falciparum and P. vivax - Talundzic, Eldin (Public Library of Science, 2015)

(untitled) (PLoS One)
Plasmodium falciparum resistance to artemisinin has emerged in the Greater Mekong Subregion and now poses a threat to malaria control and prevention. Recent work has identified mutations in the kelch propeller domain of the P. falciparum K13 gene to be associated artemisinin resistance as defined by delayed parasite clearance and ex vivo ring stage survival assays. Species specific primers for the two most prevalent human malaria species, P. falciparum and P. vivax, were designed and tested on multiple parasite isolates including human, rodent, and non- humans primate Plasmodium species. The new protocol described here using the species specific primers only amplified their respective species, P. falciparum and P. vivax, and did not cross react with any of the other human malaria Plasmodium species. We provide an improved species specific PCR and sequencing protocol that could be effectively used in areas where both P. falciparum and P. vivax are circulating. To design this improved protocol, the kelch gene was analyzed and compared among different species of Plasmodium. The kelch propeller domain was found to be highly conserved across the mammalian Plasmodium species.